Six Month Mortality in Patients with COVID-19 and Non-COVID-19 Viral Pneumonitis Managed with Veno-Venous Extracorporeal Membrane Oxygenation. Issue 9 (18th June 2021) - Garfield, Benjamin; Bianchi, Paolo; Arachchillage, Deepa; Hartley, Philip; Naruka, Vinci; Shroff, Diana; Law, Alexander; Passariello, Maurizio; Patel, Brijesh; Price, Susanna; Rosenberg, Alexander; Singh, Suveer; et al.
Abstract : A significant proportion of patients with COVID-19 develop acute respiratory distress syndrome (ARDS) with high risk of death. The efficacy of veno-venous extracorporeal membrane oxygenation (VV-ECMO) for COVID-19 on longer-term outcomes, unlike in other viral pneumonias, is unknown. In this study, we aimed to compare the 6 month mortality of patients receiving VV-ECMO support for COVID-19 with a historical viral ARDS cohort. Fifty-three consecutive patients with COVID-19 ARDS admitted for VV-ECMO to the Royal Brompton Hospital between March 17, 2020 and May 30, 2020 were identified. Mortality, patient characteristics, complications, and ECMO parameters were then compared to a historical cohort of patients with non-COVID-19 viral pneumonia. At 6 months survival was significantly higher in the COVID-19 than in the non-COVID-19 viral pneumonia cohort (84.9% vs. 66.0%, p = 0.040). Patients with COVID-19 had an increased Murray score (3.50 vs. 3.25, p = 0.005), a decreased burden of organ dysfunction (sequential organ failure score score [8.76 vs. 10.42, p = 0.004]), an increased incidence of pulmonary embolism (69.8% vs. 24.5%, p < 0.001) and in those who survived to decannulation longer ECMO runs (19 vs. 11 days, p = 0.001). Our results suggest that survival in patients supported with EMCO for COVID-19 are at least as good as those treated for non-COVID-19 viral ARDS.